2020
DOI: 10.3171/2020.2.spine191534
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing the role of adjuvant or salvage radiotherapy for spinal myxopapillary ependymomas

Abstract: OBJECTIVEThe authors sought to describe the long-term recurrence patterns, prognostic factors, and effect of adjuvant or salvage radiotherapy (RT) on treatment outcomes for patients with spinal myxopapillary ependymoma (MPE).METHODSThe authors reviewed a tertiary institution IRB-approved database and collected data regarding patient, tumor, and treatment characteristics for all patients treated consecutive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…have found a significant improvement in postrecurrence progression free survival in patients receiving salvage radiation therapy. [ 10 ] Similarly a recent study by Montero et al . showed successful tumor control after salvage therapy for initial recurrence.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…have found a significant improvement in postrecurrence progression free survival in patients receiving salvage radiation therapy. [ 10 ] Similarly a recent study by Montero et al . showed successful tumor control after salvage therapy for initial recurrence.…”
Section: Discussionmentioning
confidence: 70%
“…While many authors believe that adjuvant therapy is warranted to decrease the risk of cranio-spinal axis and extra-axial spread, others believe that close follow-up should suffice given the benign nature of these tumors. [ 2 , 4 , 6 , 10 , 11 ] Our data suggest that adjuvant therapy for patients with partially resected MPE may decrease recurrence risk. This is consistent with a study by Kukreja et al ., the rare cancer network, and others.…”
Section: Discussionmentioning
confidence: 74%
“…29,30 Securing a better balance between preservation of neurological condition after surgery and medium-term to long-term control of tumor progression is likely to receive no objections as the primary goal of surgery. Although many reports have been published on postoperative RT for myxopapillary ependymoma, [31][32][33] the role of adjuvant RT for WHO grade II or III SIE remains controversial. Several clinical studies have suggested that postoperative radiation after non-GTR can reduce the risk of recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Although many reports have been published on postoperative RT for myxopapillary ependymoma, 31-33 the role of adjuvant RT for WHO grade II or III SIE remains controversial. Several clinical studies have suggested that postoperative radiation after non-GTR can reduce the risk of recurrence.…”
Section: Discussionmentioning
confidence: 99%